Tammām Hassān Wa Ārāuhu Ḥaula Tajdīd An-Naḥwi (Dirāsah Waṣfiyyah Taḥlīliyyah Fī Kitābihi Al-Lugah Al-‘Arabiyyah Ma’nāhā Wa Mabnāhā) - Alif Cahya Setiyadi; Ummu Sa'adah (LISANUDHAD: JURNAL BAHASA, PEMBELAJARAN DAN SASTRA ARAB, 2019)
Tammām Hassān Wa Ārāuhu Ḥaula Tajdīd An-Naḥwi (Dirāsah Waṣfiyyah Taḥlīliyyah Fī Kitābihi Al-Lugah Al-‘Arabiyyah Ma’nāhā Wa Mabnāhā)Alif Cahya Setiyadi, Ummu Sa’adahUniversity of Darussalam Gontoralif.setiyadi@unida.gontor.ac.id, saadah.afhamid@gmail.com AbstractNaḥwu is a very important science in learning Arabic. Because Naḥwu was formed to keep the Arabic from the errors that spread in that era. But Naḥwu is still a difficult science to learn, it is felt to this day, that many students who have years of learning Naḥwu has not understood the science itself even worse when the learning at all can not help them understand Arabic. Hence came the renewal movements which are highly touted by Nuḥāt especially in this modern age. and which was seen most representative in his thinking between Nuḥāt in this age is Tammam Hassan. He is Arabic Linguist who has a lot of renewal ideas in Arabic especially the science of Naḥwu, and the book he has written is very much, and among the books that written by Tammam Hassan is Al-Lugah Al-‘Arabiyyah Ma’nāhā Wa Mabnāhā which considered as a phenomenal idea of Him and was a major breakthrough in the history of the Arabic language. So it the research is necessary to know the Naḥwu reforms based the thought of Tammam Hassan through one of his book Al-Lughoh Al-Lugah Al-‘Arabiyyah Ma’nāhā Wa Mabnāhā. And the values of this research are including The division of sentences into seven include Ism, Ṣiffah, Fi'l, Ḍamir, Khalifah, Ẓarf , and ‘Adāt, The Rejection the thought of ‘Amil Naḥwy and replacing it with the thought of Ta'liq through using Qarāin, Knowing the theory of incorporation of some Qarāin to produce functional meaning, Distinguishes between the times of Ṣorfi and Naḥwy fits side function, Permitted to use a Qarīnah or not use it when there are words or sentences are already showing clarity of meaning. This is why Naḥwu are expected to be able to maintain the authenticity of arabic through reforms that support the development of it.Keywords: Tammam Hassan, Nuḥāt, Naḥwu, Renewal Naḥwu, Al-Lugah Al-‘Arabiyyah Ma’nāhā Wa Mabnāhā تمام حسان وآراءه حول تجديد النحو (دراسة وصفية تحليلية في كتابه اللغة العربية معناها ومبناها)أليف تجهيا ستيادي، أمّ سعادةجامعة دار السلام كونتورalif.setiyadi@unida.gontor.ac.id, saadah.afhamid@gmail.com الملخصكان علم النحو هو علم مهم في تعلم اللغة العربية. لأن نشأته لحفظ اللسان من الخطأ الشائع عندئذٍ، ولكن مازال النحو علما صعبا في العربية، وتجد هذه الصعوبة إلى اليوم، بدليل على أنّ كثيرا من الطلاب لم يفهم النحو جيدا بعد تعلمه بضع سنين بل أشد من ذلك، يعني أن تعلمهم النحو لم يحملهم إلى فهم اللغة العربية. فمن هذا ظهرت حركة تجديدية التي دعاه النحاة في هذا العصر. ومن المشكلة الموجودة كانت من المهم أن يعرف بعض وجوه التجديد الذي حمله النحاة في هذا العصر. فكان أحسن النحاة الذي له آراء في هذا الشيء هو تمام حسان. أنه عالم لغوي الذي قد أخرج آراء كثيرة في اللغة العريية خاصة في النحو، وألف هو كتبٌ كثيرةٌ فيه. ككتاب اللغة العربية معناها ومبناها. هذا الكتاب رآه الآخرون كاختراع في اللغة العربية.  وهذا الكتاب هو آية رائعة في اللغة العربية. الهدف في كتابة هذا البحث العلمي بهذا الموضوع هو لمعرفة تجديد النحو الذي يلد من فكرة تمام حسان في أحد كتابه وهو كتاب اللغة العربية معناها ومبناها. فنتائج البحث التي حصلتها الباحثة هي أن تمام حسان قسم الكلم إلى سبعة أقسامٍ وهي الاسم، الصفة، الفعل، الضمير، الخالفة، الظرف، والأداة. أنه رفض فكرة العامل النحوي وبدله بفكرة التعليق وذلك بواسطة القرائن. أنه أنشأ نظرية تضافر القرائن ليحصل على المعنى الوظيفي. أنه فرق بين الزمن الصرفي والزمن النحوي من ناحية وظيفته. جواز الترخص في القرينة –استفادها أو عدمها- في أمن اللبس، حتى إذا لا يُستفاد أحد القرينة كان المعنى الذي وصله مفهوم مراده ومقصوده. وهذا لأن النحو ارتجى لحفظ أصالة اللغة العربية من تجديده المدافع لتطوره.الكلمة المفتاحية: تمام حسان، النحاة، النحو، تجديد النحو، كتاب اللغة العربية معناها ومبناها